2012
DOI: 10.1371/journal.pone.0036916
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Nucleotides Inhibit Insulin Receptor Signaling, Stimulate Autophagy and Control Lipoprotein Secretion

Abstract: Hyperglycemia is associated with abnormal plasma lipoprotein metabolism and with an elevation in circulating nucleotide levels. We evaluated how extracellular nucleotides may act to perturb hepatic lipoprotein secretion. Adenosine diphosphate (ADP) (>10 µM) acts like a proteasomal inhibitor to stimulate apoB100 secretion and inhibit apoA-I secretion from human liver cells at 4 h and 24 h. ADP blocks apoA-I secretion by stimulating autophagy. The nucleotide increases cellular levels of the autophagosome marker,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 53 publications
10
49
0
Order By: Relevance
“…We have previously shown that extracellular ADP blocks insulin receptor signaling and thereby stimulates cellular autophagy and perturbs protein secretion [1]. This work may therefore illustrate how nutrient deprivation initiates a cellular response to starvation through an autocrine and paracrine control of purinergic signaling.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…We have previously shown that extracellular ADP blocks insulin receptor signaling and thereby stimulates cellular autophagy and perturbs protein secretion [1]. This work may therefore illustrate how nutrient deprivation initiates a cellular response to starvation through an autocrine and paracrine control of purinergic signaling.…”
Section: Discussionmentioning
confidence: 71%
“…The extracellular nucleotide milieu thereby acts through specific P2X and P2Y receptors to promote a purinergic signaling response. Acute and short-lived nucleotide signaling is required for normal cellular function, while chronic purinergic signaling appears to have negative effects on insulin receptor (IR-β) signaling [1,33] and cellular inflammatory pathways [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,[33][34][35] Moreover, it has been previously reported that P2RY13 activation by ADP induces autophagy in hepatoma cell lines. 36 However to the best of our knowledge, this is the first description of purinergic receptor-mediated differentiation being dependent on autophagy induction.…”
Section: Discussionmentioning
confidence: 82%